Design and operation of a metal hydride reactor within a thermochemical energy store for use in concentrated solar power - Adams, Marcus J. (2021)
This thesis covers the design of a metal hydride reactor within a thermo-chemical energy store for use in concentrated solar power (CSP). Thermo-chemical energy storage has been explored to improve on existing sensible heat technologies, potentially enabling fulfilment of CSP thermal energy storage cost targets, where metal hydrides have emerged as a TCES front-runner. This work introduces a unifying model for both the hydrogenation and dehydrogenation kinetics of MgH2, through the Site Availability Model (SAM). The model expands on Langmuir’s site theory, in which a site can also be unavailable or available to react. This “unavailability” is governed by the site availability driving force, incorporating ideas such as site de-activation and strain/relaxation, which is influenced by temperature and pressure. These phenomena are proposed for both hydrogenation and dehydrogenation. In addition, SAM assumes the rate determining step is at the surface, where both hydrogenation/dehydrogenation assume a spherical surface, with dehydrogenation including the concept of particle fragmentation. The models developed, SAM:DR and SAM:ACR:SC:F, were successful in representing the kinetics of Mg hydrogenation and MgH2 dehydrogenation respectively of a small 0.2g sample, for all conditions tested. This includes conditions at close and moderately far from equilibrium for Mg hydrogenation. The SAM was also successfully applied to a 154g magnesium sample, providing confidence that the derived rate laws exhibit intensive characteristics, and assurance that the models can be used for larger scale reactor design. The implications of the thesis demonstrate the advancement in reactor design for metal hydride thermo-chemical energy storage to enable larger scale reactor designs. N.B. COVID-19 did not majorly impact the project completion, however it did disrupt the experiments on the large lab-scale reactor (chapter 6). The duration of the delay was approximately 3-4 months. It would have been desirable to run more tests and explore ways to achieve a higher operating temperature. In general, it was possible to fulfil the aims and objectives of this thesis.